2021
DOI: 10.1038/s41598-021-95741-w
|View full text |Cite
|
Sign up to set email alerts
|

Integrated biocontrol of tobacco bacterial wilt by antagonistic bacteria and marigold

Abstract: Tobacco bacterial wilt (TBW) is seriously damages the growth of tobacco. There is an urgent need to find a safer and more effective measure to control TBW. In this study, B. amyloliquefaciens ZM9 and marigold powder were applied to the tobacco roots alone or in combination, and the potential inhibition of TBW was assessed. On the other hand, the effects of these treatments on soil physicochemical properties, rhizosphere microbial community and soil metabolites were also evaluated. The results showed that the a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
2
8
0
Order By: Relevance
“…In this study, bacterial phyla, such as Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, and Firmicutes, and fungal phyla, including Ascomycota, Basidiomycota, Mortierellomycota, and Chytridiomycota, were significantly more abundant in all rhizosphere soil samples. Our results roughly corresponded to the results of previous reports that agricultural soils mainly consist of bacterial phyla Proteobacteria, followed by Acidobacteria, Actinobacteria, Bacteroidetes, Planctomycetes, Chloroflexi, and Verrucomicrobia ( 44 46 ) and fungal phyla Ascomycota followed by Basidiomycota, and Mortierellomycota or Chytridiomycota ( 43 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, bacterial phyla, such as Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, and Firmicutes, and fungal phyla, including Ascomycota, Basidiomycota, Mortierellomycota, and Chytridiomycota, were significantly more abundant in all rhizosphere soil samples. Our results roughly corresponded to the results of previous reports that agricultural soils mainly consist of bacterial phyla Proteobacteria, followed by Acidobacteria, Actinobacteria, Bacteroidetes, Planctomycetes, Chloroflexi, and Verrucomicrobia ( 44 46 ) and fungal phyla Ascomycota followed by Basidiomycota, and Mortierellomycota or Chytridiomycota ( 43 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…We found that the alpha diversity indices (Simpson, Shannon, and Shannon evenness) for soil bacterial and fungal communities were significantly higher under T2. PCoA of soil bacterial and fungal communities showed a clear separation between the treatments (CK, T1, and T2), indicating that bacterial and fungal community composition significantly differed under the application of strain WS-10, which is similar to the results of previous reports ( 41 43 ). In this study, bacterial phyla, such as Proteobacteria, Actinobacteria, Acidobacteria, Chloroflexi, and Firmicutes, and fungal phyla, including Ascomycota, Basidiomycota, Mortierellomycota, and Chytridiomycota, were significantly more abundant in all rhizosphere soil samples.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Regarded as one of the most popular commodities, merchandise corresponding to tobacco plays an important role in undertaking the national economic task. However, the tobacco-planting industry is hindered by plant diseases such as tobacco mosaic virus, tobacco black shrank, and tobacco bacterial wilt ( Hu Q. et al, 2021 ; Hu Y. et al, 2021 ). Chemicals, chemical pesticide, soil fumigation, and microbial inoculants consist of the mainstream pathogen control strategies that have earned great achievements fighting against plant diseases ( Alori and Babalola, 2018 ; Ren et al, 2018 ; Raymaekers et al, 2020 ; Long et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Soil microorganisms play an important role in soil biological functions including biogeochemical and material cycling, and degradation and transformation of organic matter 17 , 18 . Some probiotic microorganisms can also promote plant growth and suppress soil-borne diseases 19 , 20 . Notably, straw contains some readily decomposable compounds (sugars, proteins, etc.)…”
Section: Introductionmentioning
confidence: 99%